Otherness and Field of Vision: Experimentations and Reflection on a Pedagogical Practice (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This article reflects on the body and otherness in performing arts training, based on Marcelo Lazzaratto's "Field of Vision" methodology. Structured as action research and grounded in Bakhtin's dialogic philosophy, the study analyzes a theatrical improvisation workshop held at Academia Cena Hum in 2025. Using logs, photos, and videos, it examines teaching-learning dynamics, presence effects, and the chronotopic dimension in collective space. It concludes that the practice transcends technical training, shaping an ethical and aesthetic territory for self-cultivation and embracing differences.
Keywords: field of vision; otherness; presence; chronotope; listening